Aktivitas Antibakteri Minyak Jarak (Castor Oil) dalam Menghambat Pertumbuhan Bakteri Propionibacterium Acnes dan Staphylococcus Aureus - Yuni Angelia Simbolon; Julia Reveny; Masfria Masfria (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract Acne is a skin disorder caused by chronic inflammation of the pilosebaceous follicles, commonly associated with increased sebum, bacterial colonization, and local inflammation. The primary bacteria involved are Propionibacterium acnes and Staphylococcus aureus. Long-term use of synthetic antibiotics can lead to bacterial resistance, thus encouraging the search for natural-based alternatives. This study aimed to evaluate the antibacterial activity of castor oil against both bacterial species. The research applied a disc diffusion method to assess the inhibition zones, followed by tests for minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and cellular leakage analysis using UV-Vis spectrophotometry and atomic absorption spectroscopy (AAS). Results demonstrated that castor oil exhibits moderate antibacterial activity, with the highest inhibition observed at 100% concentration: 12.86 mm for P. acnes and 10.3 mm for S. aureus. Furthermore, castor oil induced leakage of Ca²⁺, K⁺, protein, and nucleic acids from bacterial cells. These findings confirm the potential of castor oil as a natural topical antibacterial agent for acne treatment.Keywords: castor oil, antibacterial, acne, Propionibacterium acnes, Staphylococcus aureus